2017
DOI: 10.1159/000477574
|View full text |Cite
|
Sign up to set email alerts
|

Serum Hyaluronic Acid Levels Are Altered in Acute Leukemia Patients: Potential Prognostic Implications

Abstract: Background: Studies on the serum concentration of hyaluronic acid (HA) in newly diagnosed patients with acute myeloid leukemia (AML), B-acute lymphoblastic leukemia (B-ALL), and mantle-cell lymphoma (MCL) are scarce. In this study, we focused on investigating whether HA could serve as a possible prognostic marker in patients with AML, B-ALL, and MCL. Methods: The serum concentration of HA was measured in a total of 51 patients with newly diagnosed AML, B-ALL, and MCL. Venous blood was collected 1 day before th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 39 publications
3
8
0
Order By: Relevance
“…Serum (n = 51) Prognosis for acute myeloid leukemia [134] Urine (n = 513) Diagnosis for bladder cancer [135] Serum (n = 63) Diagnosis for upper gastrointestinal cancers [136] Cytosol (n = 120) Prognosis for colorectal cancer [137] Tissues (n = 46)/Sputum (n = 25) Diagnosis and prognosis for lung cancer [138] Serum/pleural (n = 96) Diagnosis and prognosis for malignant mesothelioma [139] Serum (n = 506) Prognosis for liver cancer in hepatic resection [140] Tissues (n = 45) Prognosis for nerve sheath tumor [141] Enzymes HPSE Tissues (n = 182) Prognosis for glioma [142] Serum (n = 156) Diagnosis for breast cancer [143] Serum (n = 177) Diagnosis for ovarian cancer [144] Tissues (n = 81) Prognosis for oral mucosal melanoma [145] HYAL-1 Tissues (n = 407/178) Prognosis for bladder cancer [146,147] Tissues (n = 70) Prognosis for prostate cancer [148] Urine (n = 513) Diagnosis for bladder cancer [149] Tissues (n = 34) Prognosis for colorectal cancer [150] HAS1 Tissues (n = 278) Prognosis for breast cancer [151] Tissues (n = 31) Prognosis for colon cancer [152] Tissues (n = 287) Prognosis for prostate cancer [153] HAS2 Tissues (n = 407) Prognosis for bladder cancer [146] HAS3 Tissues (n = 407) Prognosis for bladder cancer [146] Tissues (n = 278) Prognosis for breast cancer [151] MMP2 Tissues (n = 1266) Prognosis for oral cancer [154] MMP3 Urinary (n = 70) Diagnosis and prognosis for bladder cancer [155] MMP9 Tissues (n = 1266) Prognosis for oral cancer [154] MMP14 Tissues (n = 456) Prognosis for colorectal cancer [156] MMP16 Tissues (n = 375) Prognosis for gastric cancer [157] Effectors RHAMM Tissues (n = 383) Prognosis for large cell lung cancer [158] Tissues (n = 64) Prognosis for kidney cancer [159] Tissues (n = 33) Prognosis for ovarian cancer [160] Tissues (n = 223) Progno...…”
Section: Samples Potential Clinical Applications In Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Serum (n = 51) Prognosis for acute myeloid leukemia [134] Urine (n = 513) Diagnosis for bladder cancer [135] Serum (n = 63) Diagnosis for upper gastrointestinal cancers [136] Cytosol (n = 120) Prognosis for colorectal cancer [137] Tissues (n = 46)/Sputum (n = 25) Diagnosis and prognosis for lung cancer [138] Serum/pleural (n = 96) Diagnosis and prognosis for malignant mesothelioma [139] Serum (n = 506) Prognosis for liver cancer in hepatic resection [140] Tissues (n = 45) Prognosis for nerve sheath tumor [141] Enzymes HPSE Tissues (n = 182) Prognosis for glioma [142] Serum (n = 156) Diagnosis for breast cancer [143] Serum (n = 177) Diagnosis for ovarian cancer [144] Tissues (n = 81) Prognosis for oral mucosal melanoma [145] HYAL-1 Tissues (n = 407/178) Prognosis for bladder cancer [146,147] Tissues (n = 70) Prognosis for prostate cancer [148] Urine (n = 513) Diagnosis for bladder cancer [149] Tissues (n = 34) Prognosis for colorectal cancer [150] HAS1 Tissues (n = 278) Prognosis for breast cancer [151] Tissues (n = 31) Prognosis for colon cancer [152] Tissues (n = 287) Prognosis for prostate cancer [153] HAS2 Tissues (n = 407) Prognosis for bladder cancer [146] HAS3 Tissues (n = 407) Prognosis for bladder cancer [146] Tissues (n = 278) Prognosis for breast cancer [151] MMP2 Tissues (n = 1266) Prognosis for oral cancer [154] MMP3 Urinary (n = 70) Diagnosis and prognosis for bladder cancer [155] MMP9 Tissues (n = 1266) Prognosis for oral cancer [154] MMP14 Tissues (n = 456) Prognosis for colorectal cancer [156] MMP16 Tissues (n = 375) Prognosis for gastric cancer [157] Effectors RHAMM Tissues (n = 383) Prognosis for large cell lung cancer [158] Tissues (n = 64) Prognosis for kidney cancer [159] Tissues (n = 33) Prognosis for ovarian cancer [160] Tissues (n = 223) Progno...…”
Section: Samples Potential Clinical Applications In Cancermentioning
confidence: 99%
“…High expression levels of HS signaled poor prognosis in patients with gastric carcinoma [131]. Higher levels of HA were associated with poor survival in patients with breast cancer [133], acute myeloid leukemia [134], and prostate cancer [132]. Elevated serum levels of HA can be a diagnostic biomarker for patients with prostate cancer [132], upper gastrointestinal cancers [136], and mesothelioma [139].…”
Section: Gags and Gps In Diagnosis And Prognosismentioning
confidence: 99%
“…Although HA and collagen expression in the TME are considered prognostic biomarkers, there are no/few studies examining serum concentrations of HA and type III collagen in patients with PC. Previous studies conducted in other malignancies have shown a negative correlation between serum HA and outcome and serum collagen fragments and outcome . The aim of this biomarker study was to investigate the clinical utility of serum HA and propeptide of type III collagen (PRO‐C3) in patients with PC.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we confirmed that up-regulated UGDH nuclear or cytoplasmic expression was observed in stage I ACs compared with non-neoplastic bronchial epithelial cells. A recent study showed that the serum HA level was correlated with the metastasis and aggressiveness of tumors (1,35). There is no report on serum UGDH levels in cancer patients, but the expression levels may be elevated because overexpression of UGDH in tumor cells is detected.…”
Section: Discussionmentioning
confidence: 99%